THE NEGOTIATION OF KEY ACTORS TOWARDS PETE-PETE (MINIBUS PUBLIC TRANSPORT) INTEGRATION IN MAMMINASATA BRT - Muhammad Saifullah; Isabella (Citra Institute, 2023)
Trans Mamminasata BRT in South Sulawesi is one of the national priority transportation program to solve traffic congestion in the region. The BRT operation will have a challenge since it is impacted the existing minibus public transport (Pete-pete). Many drivers have done several demonstrations against the BRT operation. Therefore, the negotiation strategy is need to be designed and implemented to realize this BRT program as all stakeholder’s goals. The objective of this study that used literature review method is to find out the most appropriate scheme options for Pete-pete’s actors (drivers and owners) to be integrated with Trans Mamminasata BRT system based on lessons learned from previous cases that occurred in DKI Jakarta Province and Semarang City through a negotiation process between dispute parties. For further studies, we suggest doing research to gain an existing players perspective on the BRT transition and testing the transition package as part of the negotiation. Key words: BRT, negotiation, transportation, bus reform, Mamminasata